Wpływ środowisk socjalizacji na cele życiowe młodocianych przestępców = Influence of socialization surroundings on juvenile delinquents - Magda, Ernest (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article comes from the need of revealing the personality of juvenile delinquents who have infringed the law in prospect of a purposeful activity.
Keywords: socjalizacja; niedostosowanie społeczne; młodzież; przestępczość nieletnich